Da negação à integração: um estudo da trajetória política do Partido dos Trabalhadores (1979-2002) - Lopes, Walson (2009)
The Workers' Party (Partido dos Trabalhadores) began in the early 1980's. At the time, the focus of its political discourse was the struggles for the historical and immediate interests of the working class. This struggle would be independent of the capitalist class and the bourgeois State. According to its first documents, PT's strategic objective was to build a society without exploitation and exploiters . In short, it was founded a party that presented itself as deeply linked to working class, autonomous and socialist, although there were very imprecisions about this last aspect. Moreover, there was a great concern in defending a democratic structure in the party. In thesis, all the militants would have the right to participate effectively of the decisions. However, these seminal characteristics disappeared from PT's political practices and ideas. Focusing on the political trajectory of PT (1979-2002), this research aims to contribute to identify and to analyze some of the innumerable aspects of this process of transformation and capitulation of the Workers' Party